The value of reflection on the evolving individual and collective practice of public policy innovation in water management: An action science approach. (10th January 2018) - Duijn, Michael
Abstract: This article examines the impacts of reflection on the practice of public policy innovation for water management. The reflection is provided for a specific community of practitioners, the professionals involved in an innovation program of the Dutch ministry of Public Works and Water Management. Innovation is perceived necessary for developing and promoting new solutions for the challenges in water management, induced by climate change. Instead of blocking water through technical solutions grounded in civil and hydraulic engineering, alternative approaches such as spatial accommodation of water, building with nature and multi-layered safety must become equally feasible. The community agreed that regular reflection was needed to learn from their experiences. Learning could guide them in changing, and if possible, improving their innovation practice. Action science delivers knowledge based on which intervention can be designed to promote change in a community of practitioners, thus enhancing the community's capacity to learn. Here, the theory of action assumes that reflection will inform change in innovation practice, if perceived necessary by the community of practitioners involved. Reflection was provided during a period of two and a half years. Its impacts were evaluated through in-depth interviews with the participating professionals. The needs for reflection were assessed in an ex ante evaluation. The impacts of reflection provided were assessed in two ex durante evaluations and an ex post evaluation. The ex post evaluation indicates an important impact on separate aspects of the individual innovation practice of the professionals involved. The impact on the development of a collective innovation practice is limited but important: the realignment of the program's substantive focus during its implementation. Interpreting the impacts of reflection made clear that reflection helps to identify the possibilities for improvement and guides their targeted implementation in practice.